Ultra‐high‐resolution inelastic X‐ray scattering at high‐repetition‐rate self‐seeded X‐ray free‐electron lasers. (12th February 2016) - Chubar, Oleg; Geloni, Gianluca; Kocharyan, Vitali; Madsen, Anders; Saldin, Evgeni; Serkez, Svitozar; Shvyd'ko, Yuri; Sutter, John
Abstract : This article explores novel opportunities for ultra‐high‐resolution inelastic X‐ray scattering (IXS) at high‐repetition‐rate self‐seeded XFELs. These next‐generation light sources are promising a more than three orders of magnitude increase in average spectral flux compared with what is possible with storage‐ring‐based radiation sources. In combination with the advanced IXS spectrometer described here, this may become a real game‐changer for ultra‐high‐resolution X‐ray spectroscopies, and hence for the studies of dynamics in condensed matter systems. Abstract : Inelastic X‐ray scattering (IXS) is an important tool for studies of equilibrium dynamics in condensed matter. A new spectrometer recently proposed for ultra‐high‐resolution IXS (UHRIX) has achieved 0.6 meV and 0.25 nm −1 spectral and momentum‐transfer resolutions, respectively. However, further improvements down to 0.1 meV and 0.02 nm −1 are required to close the gap in energy–momentum space between high‐ and low‐frequency probes. It is shown that this goal can be achieved by further optimizing the X‐ray optics and by increasing the spectral flux of the incident X‐ray pulses. UHRIX performs best at energies from 5 to 10 keV, where a combination of self‐seeding and undulator tapering at the SASE‐2 beamline of the European XFEL promises up to a 100‐fold increase in average spectral flux compared with nominal SASE pulses at saturation, or three orders of magnitude more than what is possible with storage‐ring‐based radiation sources. Wave‐optics calculations show that about 7 × 10 12  photons s −1 in a 90 µeV bandwidth can be achieved on the sample. This will provide unique new possibilities for dynamics studies by IXS.